Characteristics of water stable isotopes and runoff sources of a small permafrost basin in northeastern China - Zhang, Boxiong; Zang, Shuying; Zhao, Lin; Wu, Xiaodong; Liu, Rui; Dong, Xingfeng; Yang, Dongyu; Cheng, Xiaofeng (Frontiers in Earth Science, 2024)
Permafrost degradation may have significant impacts on regional water cycles, while little is known about the recharge sources of runoff in permafrost regions, hindering our capability to predict river discharges. Here, a small permafrost basin in Northeast China was selected as the study area. We analyzed isotopic tracers of 186 precipitation, river water, and supra-permafrost water samples collected from May to October 2021. We further calculated the contribution of supra-permafrost water and precipitation to river discharges. The δ18O and δD of precipitation exhibited a significant correlation with air temperature (p<0.05). Similar values and trends were observed in the stable isotope changes of river water and supra-permafrost water, indicating a close hydraulic relationship between the two water sources. Hydrograph separation revealed that supra-permafrost water and precipitation are the first and second end-member of river water in the basin, with a contribution of 85% and 15%, respectively. Overall, our results suggest that supra-permafrost water is the main recharge source of runoff, highlighting the importance of permafrost in the regulation of runoff in small catchments.